The Effect Addition of Soil Amandments and PGPR (Plant Growth Promoting Rhizobacteria) on the Growth and Yield of Cotton Plants Intercropped with Corn Plants in Dry Land of North Lombok Regency of Indonesia - Siti Rohmaniati, Baiq; Sarjan, M.; Suwardji, Suwardji (International Journal of Science, Technology & Management, 2024)
This research investigates the effect of soil amendments in the form of cow, form goat manures and PGPR biofertilizer on cotton plants intercropped with corn in the dry lands of North Lombok Regency. The research aims is to determine the growth and yield response of cotton plants due to the application of soil amendments and PGPR in an intercropped system with corn in dryland areas. The research was conducted from December 2023 to June 2024 in Andalan Village, Bayan District, North Lombok Regency. The method used is an experimental method with field trials. The design used was Randomized Block Design (RBD), incorporating two factors: soil amendment treatment (P) as the main plot and PGPR (K) concentration treatments as the subplot. Soil amendments consisted of three levels: P0 (no cow manure and no goat manure), P1 (20 tons/ha cow manure), P2 (20 tons/ha goat manure). PGPR concentration consisted of four levels: K0 (without PGPR), K1 (20 ml/liter PGPR application), K2 (30 ml/liter PGPR application), and K3 (40 ml/liter PGPR application). The research results indicated that the application of 20 tons/ha of goat manure (P2) produced the highest average across all observed parameters (plant height, number of leaves, branch number, stem diameter, and plant yield). Similarly, the application of 40 ml/liter PGPR produced the highest average for these observed parameters. Based on the results of the land equivalent ratio (LER) analysis, this integration system shows highly suitable and relevant to be applied in the dry lands of North Lombok.